(untitled) (Health Renaissance, 2011)
Congenital absence of gall bladder is a very rare abnormality which is usually identified accidentally. Ultra sonography is the main diagnostic tool. It has good prognosis. Health Renaissance, May-Aug 2010; Vol 8 (No.2):130-132